TEKANAN ANGGARAN WAKTU MEMODERASI LOCUS OF CONTROL INTERNAL PADA PERILAKU UNDERREPORTING OF AUDIT TIME - Yuliani, Gusi Made Dwi Oka; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
The aim of this research is to investigase the impact of internal locus of control on underreporting of audit time behavior and time budget pressure in moderating the impact of internal locus of control on underreporting of audit time behavior. This research was conducted to the auditors who work in the public accounting firm of Bali Province. Sampling taking of this research is determined by method of non-probability sampling with purposive sampling technique. Method of collecting data is using survey method. The sample size of this research is 53 respondents. The data analysis technique used in this study is Moderating Regression Analysis (MRA). All variables of this research is valid and reliable. The research data is qualifies that the distribution of data are normal and the models used do not contain any heteroskedastisitas. Based on the results of the analysis of this study found that the internal locus of control has negative and significant effect on underreporting of audit time behavior. Time budget pressure reinforce internal locus of control influence on underreporting of audit time behavior.
Keywords: Internal Locus of Control; Time Budget Pressure; Underreporting of Audit Time Behavior